An energetic orphan in an endocrine tissue: A revised perspective of the function of estrogen receptor‐related receptor alpha in bone and cartilage. (15th January 2013) - Bonnelye, Edith; Aubin, Jane E
Abstract: Estrogen receptor‐related receptor alpha (ERRα) is an orphan nuclear receptor with sequence homology to the estrogen receptors, ERα/β, but it does not bind estrogen. ERRα not only plays a functional role in osteoblasts but also in osteoclasts and chondrocytes. In addition, the ERRs, including ERRα, can be activated by coactivators such as peroxisome proliferator‐activated receptor‐gamma coactivator‐1 (PGC1α and β) and are implicated in adipogenesis, fatty acid oxidation, and oxidative stress defense, suggesting that ERRα—through its activity in bone resorption and adipogenesis—may regulate the insulin and leptin pathways and contribute to aging‐related changes in bone and cartilage. In this review, we discuss data on ERRα and its cellular and molecular modes of action, which have broad implications for considering the potential role of this orphan receptor in cartilage and bone endocrine function, on whole‐organism physiology, and in the bone aging process. © 2013 American Society for Bone and Mineral Research